A mitochondrial genome assembly of the opal chimaera, Chimaera opalescens Luchetti, Iglésias et Sellos 2011, using PacBio HiFi long reads. Issue 3 (4th March 2022) - Vilas-Arrondo, Nair; Gomes-dos-Santos, André; Pérez, Montse; Baldó, Francisco; Veríssimo, Ana; Catarino, Diana; Machado, André M.; Román-Marcote, Esther; Bañón, Rafael; Froufe, Elsa; Castro, L. Filipe C.
Abstract: Chondrichthyans (sharks, rays and chimeras) are a fascinating and highly vulnerable group of early branching gnathostomes. However, they remain comparatively poorly sampled from the point of view of molecular resources, with deep water taxa being particularly data deficient. The development of long-read sequencing technologies enables the analysis of phylogenetic relationships through a precise and reliable assembly of complete mtDNA genomes. The sequencing and characterization of the complete mitogenome of the opal chimera Chimera opalescens Luchetti, Iglésias et Sellos 2011, using the long-read technique PacBio HiFi is presented. The entire mitogenome was 23, 411 bp long and shows the same overall content, i.e. 13 protein-coding genes, 22 transfer RNA and 2 ribosomal RNA genes, as all other examined Chondrichthyan mitogenomes. Phylogenetic reconstructions using all available Chondrichthyan mitogenomes, including 11 Holocephali (chimeras and ratfishes), places C. opalescens within the Chimaeridae family. Furthermore, the results reinforce previous findings, showing the genus Chimera as paraphyletic and thus highlighting the need to expand molecular approaches in this group of cartilaginous fishes.